Compliance with personal protective equipment use among clay works employees - Niyitegeka, J.; Kibirige, I.; Mutekanga, D. R. (Edelweiss Applied Science and Technology, 2025)
This study examined how personal factors—knowledge and attitudes—and company factors—commitment, availability of personal protective equipment (PPE), adequacy of equipment, and work arrangements—are compliant with the use of PPE among Clay Works factory employees. Failure to comply results in occupational health problems. Hence, there is a need to examine both personal and institutional factors in this factory. The study employed descriptive and analytical cross-sectional research designs with qualitative and quantitative data collection approaches. Data were collected from a purposively selected 133 employees and 5 management staff of Unique Clay Works Limited. Quantitative data were collected using a questionnaire, which was distributed to all 133 respondents. Qualitative data were collected using face-to-face interviews. Quantitative data were analyzed using descriptive statistics, and qualitative data were analyzed using coding. The results show that the level of compliance with the use of PPE was low (30.1%). The regression-adjusted odds ratio shows that females are 4.95% more likely to comply than males. At the same time, commitment by management accounted for 17.56% (p < 0.05). It is recommended that employers consider gender as an important factor regarding PPE compliance in the company and that companies uphold PPE compliance and also assess productivity as a consequence of compliance.